2015
DOI: 10.21273/jashs.140.4.308
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Genetic Diversity of Common Bean from the Western Balkans

Abstract: In this study, genetic diversity of 119 accessions of common bean (Phaseolus vulgaris) from five former Yugoslav republics constituting the western Balkans was assessed by 13 microsatellite markers. This set of markers has proven before to efficiently distinguish between bean genotypes and assign them to either the Andean or the Mesoamerican gene pool of origin. In this study, 118 alleles were detected or 9.1 per locus on average. Four groups (i.e., Slovene, Croatian, Bosnian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
38
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 41 publications
9
38
2
1
Order By: Relevance
“…Mesoamerican bean genotypes can be distinguished by longer flowering times and small seeds, while Andean genotypes have large and colorful seeds [21,22]. Phylogenetic studies and evaluation of common bean genotypes collected from different regions, ranging from the Americas, Africa [23,24] and Europe [25][26][27][28], have confirmed independent domestication events specific to each of the gene-pools [20,29].…”
Section: The Diverse Common Bean Germplasm As a Potential For Discovementioning
confidence: 90%
See 1 more Smart Citation
“…Mesoamerican bean genotypes can be distinguished by longer flowering times and small seeds, while Andean genotypes have large and colorful seeds [21,22]. Phylogenetic studies and evaluation of common bean genotypes collected from different regions, ranging from the Americas, Africa [23,24] and Europe [25][26][27][28], have confirmed independent domestication events specific to each of the gene-pools [20,29].…”
Section: The Diverse Common Bean Germplasm As a Potential For Discovementioning
confidence: 90%
“…Common bean was introduced in Europe centuries ago by independent domestication events from both major centers of origin [25][26][27][28]. Our phylogenetic studies shed more light on the understanding of dissemination pathways and the evolution of this species in central Europe and have been focused on the germplasm from the Central European, South East European and Balkan region [27,28,30]. Evaluations of genetic diversity and the population structure of 167 historical and current accessions with the different geographical origin (Slovenia, Austria, Bosnia and Herzegovina, Croatia, Macedonia and Serbia) have revealed great allelic polymorphism in 14 SSR markers.…”
Section: The Diverse Common Bean Germplasm As a Potential For Discovementioning
confidence: 99%
“…Simple Sequence Repeats (SSRs) are especially suitable for genetic diversity studies due to their abundance in genome, high reproducibility and codominant nature (RAGGI et al, 2013). LIOI et al (2012) and MARAS et al (2015) have used these types of markers in common bean germplasm characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, common bean is known for its morphological variability and adaptability to different environments, creating a wide range of local varieties or landraces, as well as different technological quality of seeds (Perina et al, 2014). Moreover, studies carried out using phaseolin type as a discriminator showed that both gene pools are present in Europe, with a higher frequency of the Andean type (Bellucci et al, 2014;Maras et al, 2015). In many European countries, the selective pressure operated by farmers over time on the common bean genetic pool of introduced accessions led to the creation of well adapted landraces (Piergiovanni and Lioi, 2010).…”
Section: Sažetak Introductionmentioning
confidence: 99%